Amate' papel de corteza Mexicano [Trema micrantha (L.) Blume]: nuevas estrategias de extraccion para enfrentar las demandas de mercado - López, C. (Center for International Forestry Research, 2004)
Amate is an indigenous hand made paper manufactured in Mexico since pre-Hispanic times and distributed as handicraft since the end of the 1960s. Otomi artisans living in the mountainous region of the Sierra Norte of the State of Puebla manufacture it while numerous traders commercialize it at national and international level. Right from early days of commercialization, there has been a persistent market demand that have implied distinct changes, like constant diversification of paper product types and of trading options, involvement of new and more social actors occupied in bark harvest, paper manufacture, paper decoration, or paper trading, and the constant adaptation to new forms of work organization. As the market demand rises there are increasing pressures on tree resources to augment the bark supply. Three main processes have occurred in the Sierra Norte de Puebla region, in order to satisfy the demand for bark raw material: a) incorporation of an increasing number of harvesters b) constant search for, and adoption of, new tree species to supply bark c) the gradual spatial expansion of the harvest area. The survival of this indigenous industry, previously expected to disappear because of the scarcity of raw material, is now based on a new tree resource use strategy that consists of the exploitation of Trema micrantha trees, attaining ecologic benefits, and growing as shade trees in coffee plantations, the third most important land use of the Sierra Norte de Puebla region.